ОСОБЛИВОСТІ ІНСТИТУЦІЙНОГО ЗАБЕЗПЕЧЕННЯ СТАЛОГО РОЗВИТКУ СІЛЬСЬКОГОСПОДАРСЬКИХ ПІДПРИЄМСТВ (International Journal of Innovative Technologies in Economy, 2018)
Agriculture is an important branch of the Ukrainian economy. Its’ development directly affects the country’s food security. The defining concept of the development of this industry is the concept of sustainable development. Sustainable development is a model of society’s development, which involves establishing a balance between satisfying the needs of mankind and protecting the interests of future generations. Three main components lie in the basis of the concept of sustainable development - economic, environmental and social. However, the implementation of the key aspects of sustainable development requires the appropriate institutional support that is explored in this article.